Per Jacobsson Lecture : September 2011. (per Jacobson lecture, 2012)
This paper discusses that as the IMF had been designed to assist countries with current account deficits, its role came under discussion. It subsequently regained some importance during the Latin American crises in the 1980s and the emerging market crises in the 1990s. It became apparent that an initially national crisis might very quickly assume a global character by spreading through closely linked financial systems. The global financial system and the global real economy are so intertwined that a financial crisis can severely affect the real economy in both emerging and advanced economies. Emerging economies acted as an important stabilizer at the height of the crisis, whereas major advanced economies are now facing a rather modest outlook for growth. The ultimate objective should be to tackle the roots of the crisis instead of just creating ever more instruments to fight the symptoms. Against this backdrop, any attempt to enhance the IMF's capacity for crisis management has to be thoroughly assessed in terms of costs and benefits.